ASPECTS OF LIPID-LOWERING THERAPY WITH ATORVASTATIN IN PATIENTS WITH MYOCARDIAL INFARCTION FROM THE PERSPECTIVE OF PERSONALIZED MEDICINE - M. V. Solodun; S. S. Yakushin (Рациональная фармакотерапия в кардиологии, 2015)
Aim. To analyze the impact of the SLCO1B1*5 (c.521T> C) and LIPC (C514T) genes polymorphisms on the efficacy of atorvastatin therapy and the incidence of the combined endpoint in patients after myocardial infarction (MI). Material and methods. 121 patients with MI aged 45-75 years were included into the study. All patients were prescribed atorvastatin. A group of 65 people in whom lipid levels were studied at baseline and after 3 months of atorvastatin treatment was formed to evaluate the efficacy of statin therapy. Genetic polimorphism of SLCO1B1*5 (c.521T> C) and LIPC (C514T) was determined using polimerase chain reaction. The prognosis was assessed by clinical outcomes after 3 months of follow-up, based on the achievement of the combined endpoint MACE (Major Adverse Cardiac Events), which included cardiovascular deaths, recurrent MI, hospitalization for progressive angina, unplanned coronary revascularization. Results. Patients with SLCO1B1 c.521СC genotype had no significant reduction in the levels of atherogenic lipids (p>0.05), while patients with TT and TC genotypes demonstrated significant reduction in atherogenic cholesterol fractions (p<0.05). Allelic polymorphism of LIPC (C514T) gene has no influence on the atorvastatin treatment efficacy. The SLCO1B1 and LIPC (C514T) genes polymorphism has no impact on the three-month prognosis after MI. Conclusion. The SLCO1B1 polymorphism should be taken into consideration while personalised prescribing of atorvastatin to patients with MI.